2013
DOI: 10.1093/cvr/cvt196
|View full text |Cite
|
Sign up to set email alerts
|

Urotensin-II promotes vascular smooth muscle cell proliferation through store-operated calcium entry and EGFR transactivation

Abstract: Our data show for the first time that UII-induced VSMCs proliferation and CREB activation requires a complex signalling pathway that involves on the one hand SOCE mediated by STIM1, Orai1, and TRPC1, and on the other hand EGFR, ERK, and CaMK activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
63
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 36 publications
1
63
0
1
Order By: Relevance
“…The latter are likely activated secondarily to store depletion and Ca 2ϩ entry through Orai1 channels (e.g., direct activation by Ca 2ϩ or Ca 2ϩ -dependent delivery to the PM of TRPC-containing vesicles) (11,12,17,91). Consistent with this notion, coimmunoprecipitation experiments showed that urotensin II enhanced the STIM1-Orai1 and Orai1-TRPC1 interactions in cultured aortic SMCs (73). Rodriguez-Moyano et al (73) also showed that pharmacological inhibition of SOCE (by 50 M 2-APB or 10 M ML-9) significantly inhibited epidermal growth factor receptor and ERK phosphorylation in response to urotensin II.…”
Section: Soce In Smooth Musclementioning
confidence: 63%
See 4 more Smart Citations
“…The latter are likely activated secondarily to store depletion and Ca 2ϩ entry through Orai1 channels (e.g., direct activation by Ca 2ϩ or Ca 2ϩ -dependent delivery to the PM of TRPC-containing vesicles) (11,12,17,91). Consistent with this notion, coimmunoprecipitation experiments showed that urotensin II enhanced the STIM1-Orai1 and Orai1-TRPC1 interactions in cultured aortic SMCs (73). Rodriguez-Moyano et al (73) also showed that pharmacological inhibition of SOCE (by 50 M 2-APB or 10 M ML-9) significantly inhibited epidermal growth factor receptor and ERK phosphorylation in response to urotensin II.…”
Section: Soce In Smooth Musclementioning
confidence: 63%
“…Consistent with this notion, coimmunoprecipitation experiments showed that urotensin II enhanced the STIM1-Orai1 and Orai1-TRPC1 interactions in cultured aortic SMCs (73). Rodriguez-Moyano et al (73) also showed that pharmacological inhibition of SOCE (by 50 M 2-APB or 10 M ML-9) significantly inhibited epidermal growth factor receptor and ERK phosphorylation in response to urotensin II. Reciprocally, pharmacological inhibition of epidermal growth factor receptor and ERK inhibited the Ca 2ϩ increase and proliferation of cultured aortic SMCs in response to urotensin II.…”
Section: Soce In Smooth Musclementioning
confidence: 86%
See 3 more Smart Citations